Nature and the City in Three Norwegian Picturebooks - Katarzyna A. Tunkiel (Barnelitterært Forskningstidsskrift)
Representations of urban environments are not very common in Norwegian picturebooks, yet they allow for a nuanced understanding of how nature functions in picturebook iconotexts. This article aims to examine the relationship between nature and the city in the following works: Anda i ødemarka (2012) by Ragnar Aalbu, Fugl (2013) by Lisa Aisato, and Glassklokken (2010) by Bjørn Arild Ersland and Lilian Brøgger. Drawing upon the notion of the chronotope (Bakhtin, 1981), particularly Nikolajeva’s (1996) writings on the chronotope in children’s literature as well as Gifford’s (1999; 2012; 2014) scholarship on the pastoral and post-pastoral, the article provides an ecocritical reading of these picturebooks, inspired by some of the key questions of ecocriticism (Glotfelty, 1996). The analysis considers both the narrative and visual dimensions of the iconotexts, making it possible to shed light on environmental issues addressed in the books.